The potency of kitolod leaves (Hipobroma longiflora) as traditional medicine for conjunctivitis during the COVID-19 pandemic: a brief review - Yuliana; Ni Made Ersi Dwitami Barsua; Made Wulan Virgioni Putri; I Nyoman Satya Mahayana Putra (Indonesian Journal of Pharmacology and Therapy, 2023)
During the coronavirus disease 2019 (COVID-19) pandemic, most activities have transformed into digital ones, including computer usage. The digital screen on the computer has blue light radiation which can activate inflammatory cytokines of the eye surface and cause various disorders including includes conjunctivitis. Kitolod leaves (Hippobroma longiflora) have been used traditionally to treat conjunctivitis. This paper aimed to describe the potency of kitolod leaves for conjunctivitis. This is a narrative literature review using publications gathering from PubMed and Google Scholar published since 2013 with exclusion criteria were the animal studies. The keywords of COVID-19 pandemic, blue light, conjunctivitis, H. longiflora, traditional therapy were used. Boolean logic "AND" was used to find specific international scientific publications in PubMed. Forty selected publications were gathered, summarized and then narrated. The kitolod leaves contains bioactive substances i.e. flavonoids, alkaloids, and saponins which can inhibit S. aureus growth as the main cause of conjunctivitis. The mechanism of antibacterial of these bioactive substances through inhibition of nucleic acid synthesis, disruption of cytoplasmic membrane function, and inhibition of energy formation process. Kitolod leaves is potential to develop as traditional medicine for conjunctivitis. However, further studies are required to obtain the best standardized extract and to evaluate its clinical efficacy and safety.